CRISPR/Cas9‐mediated sheep MSTN gene knockout and promote sSMSCs differentiation. Issue 2 (22nd September 2018) - Zhang, Yani; Wang, Yingjie; Yulin, Bi; Tang, Beibei; Wang, Man; Zhang, Chen; Zhang, Wenhui; Jin, Jing; Li, Tingting; Zhao, Ruifeng; Yu, Xinjian; Zuo, Qisheng; et al.
Abstract: Myostatin ( MSTN ) is an important gene involved in the regulation of embryonic muscle cells and adult muscle development; it has a good application prospect in transgenic animal production by improving the yield of muscle. The purpose of this study is to construct MSTN gene knockout vector using clustered regularly interspaced short palindromic repeats ( CRISPR )/CRISPR‐associated protein 9 ( Cas9 ). The knockout efficiency was evaluated in sheep ear fibroblasts (SEFs) by cleavage activity of transcription of guide RNA ( gRNA ), luciferase‐single‐strand annealing assay, T7 endonuclease I assay (T7E1), and TA clone sequence (10/38); and above all, detection showed that the cleavage activity of CRISPR/Cas9 ‐mediated MSTN reached 29%. MSTN‐Cas9/gRNA4 was transfected into sheep skeletal muscle satellite cell (sSMSC) to confirm the function of MSTN in myotomes formation induced by starvation in low‐serum medium. The results showed that myotubes formation efficiency were 11.2 ± 1.3% and 19.5 ± 2.1% in the control group and knockout group, respectively. The average length of myotomes was 22 ± 5.3 and 47 ± 3.6 μm, displaying that MSTN knockout can promote sSMSC differentiation in number and length. The unlabeled MSTN‐Cas9/gRNA4 was transfected into SEFs and monoclonal positive cells was obtained after 48 hours transfection. The MSTN‐positive cells were used as donor cells to perform somatic cell nuclear transplantation to produce transgenic sheep. A total of 20 embryos were transplanted into surrogate mothers, four of them normally produce offspring. The genomic DNA of surviving lambs were used as a template, three positive individuals were identified by T7E1 digestion. All the results demonstrated that the CRISPR/Cas9 system has the potential to become an important and applicable gene engineering tool in animal breeding.